Comparative analysis of casein complex and amino acid composition in single-humped and double-humped camel milk: Implications for dairy camel breeding - Kuanysh Syman; Raissa Utegaliyeva; Abdreshov Serik Nauryzbaevish; Zharylkassynova Zhazira; Aytzhanova Mira Onlanbekovna; Kalekeshov Askar Maralovich; Mamataeva Aigul Tumaevna (Caspian Journal of Environmental Sciences)
The purpose of this work is to study the casein complex of camel milk and their amino acid composition. including the chemical composition and physico-chemical properties of milk of single-humped and double-humped camels, as well as the fractional composition of milk proteins of two types of camels and combined milk, followed by the amino acid composition of the casein complex of milk. The protein composition of the casein complex and whey proteins can be used in breeding work in dairy camel breeding to select the most desirable types of animals. The electrophoretic picture of casein fractions on polyacrylamide gel can serve as a reference in the study of camel milk proteins.